Analysis of manganes deposits on Leg XV - Thomas W Donnelly; G Nalli (PANGAEA, 1973)
The sediments of Leg 15 included several noteworthy occurrences of authigenic, volcanic and continentally derived minerals. Of these, the occurrence of native copper in pelagic clays, the relatively well developed crystals of clinoptilolite in several older volcanic clays, the widespread authigenic K-feldspar, and the occurrences of garnet (one of which appears to be authigenic; the other, not positively identified, may be volcanic) are especially interesting. At Site 150 of Leg 15 several nodules were found in Cores 4 and 5 at subbottom depths of about 100 to 115 meters. It is not certain from the occurrence whether these nodules were a) buried, having grown elsewhere, or b) were found in their present position as a result of drilling disturbance. The depth of the occurrence appears to preclude the last possibility.
Supplement to: Donnelly, TW; Nalli, G (1973): Mineralogy and Chemistry of Caribbean Sediments. In: Edgar, N.T.; Saunders, J.B.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XV, 929-962, https://doi.org/10.2973/dsdp.proc.15.127.1973